Novel NiS cocatalyst decorating ultrathin 2D TiO2 nanosheets with enhanced photocatalytic hydrogen evolution activity. (March 2017) - Xin, Yongji; Lu, Yan; Han, Changcun; Ge, Lei; Qiu, Ping; Li, Yujing; Fang, Siman
Graphical abstract: Highlights: NiS/TiO2 nanosheets photocatalysts were prepared via an in-situ synthesis approach. The highest H2 -production rate of NiS/TiO2 nanosheets is enhanced by 36 times. The photocatalytic mechanism of NiS/TiO2 nanosheets is confirmed by SPV results. Abstract: In this paper, ultrathin 2D TiO2 nanosheets which modified with ultrafine dispersions of NiS cocatalyst were successfully prepared via a low-cost and in-situ synthesis approach. The physical and chemical properties of the as-obtained NiS/TiO2 nanosheets samples were investigated by a variety of analytical techniques. Cooperated with the photocatalytic hydrogen evolution tests and surface photovoltage spectroscopy (SPV) experiments, it can be deduced that the NiS is an efficient cocatalyst, which significantly limited the recombination of photogenerated electron-hole pairs in ultrathin 2D TiO2 nanosheets and consequently improve the hydrogen evolution activity. The influence of different molar ratios of NiS on the photocatalytic activity was explored and the 5 mol% NiS/TiO2 composite photocatalyst showed the highest photoactivity which the corresponding H2 -production rate was 313.6 μmol h −1 g −1 under the UV–vis light irradiation. The optimal H2 evolution rate is 36 times as much as the value of pure TiO2 nanosheets. The photocatalytic mechanism of NiS cocatalysts on the enhanced performance of the photocatalytic activity of TiO2 nanosheets is proposed and confirmed by SPV results.